2016
DOI: 10.15412/j.jpcp.06040305
|View full text |Cite
|
Sign up to set email alerts
|

Group Positive Psychotherapy Effect on Increasing the Happiness of Mothers of Children with Cochlear Implant

Abstract: Objective: The present study aimed to investigate the effects of group positive psychotherapy on increasing the happiness of mothers of children with cochlear implants. Methods:This study was a quasi-experimental research with pretest-posttest, a control group, and a 75-day follow-up design. A total of 20 mothers of children with cochlear implants treated in Baqiyatallah Hospital of Tehran City were randomly assigned to 2 groups (10 participants in the experimental and 10 participants in the control group). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Research studies have shown that it is possible to train children and adolescents to learn the required skills to implicate optimism and reality-based positive thinking according to their psychological problems and to manage the mental tensions and problematic situations (Seligman & Csikszentmihalyi, 2014;Stewart, Watson, Clark, Ebmeier, & Deary, 2010). positive psychotherapy refers to using positive thinking interventions to deal with depression by encouraging positive emotions, raising the level of positive engagement in life, and increasing the meaning of life (Falakaflaki & Malekitabar, 2016). These people would like to pay more attention to their merits and resources, rather than the possibility of failure and problems (Ji, Holmes, & Blackwell, 2017;Khodabakhsh, Khosravi, & Zarrinpour, 2015).…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Research studies have shown that it is possible to train children and adolescents to learn the required skills to implicate optimism and reality-based positive thinking according to their psychological problems and to manage the mental tensions and problematic situations (Seligman & Csikszentmihalyi, 2014;Stewart, Watson, Clark, Ebmeier, & Deary, 2010). positive psychotherapy refers to using positive thinking interventions to deal with depression by encouraging positive emotions, raising the level of positive engagement in life, and increasing the meaning of life (Falakaflaki & Malekitabar, 2016). These people would like to pay more attention to their merits and resources, rather than the possibility of failure and problems (Ji, Holmes, & Blackwell, 2017;Khodabakhsh, Khosravi, & Zarrinpour, 2015).…”
Section: Plain Language Summarymentioning
confidence: 99%